"Women timpanist": a study about female orchestral percussionist in Spain (1990-2019) (Revista Argentina de Musicología, 2023)
Percussion has been a musical specialty linked to the ‘masculine’ and its feminization is being slow, especially in certain areas such as professional orchestras. After discovering some historical precedents and that the number of orchestral women percussionists has barely increased in almost 30 years in Spain, the main objective of this work is to know the opinions, experiences and perceptions of the percussionists themselves about the incorporation of women into this field and on their own work as professionals. With a mixed methodology, the study combines the collection of data on the distribution of the sexes on said instrument in the orchestras, an online survey and 10 in-depth face-to-face interviews. Abundant topics are addressed and emege, such as the way we “choose” our instrument, the influence of gender in the career, the feminization of percussion, the weight of stereotypes and the problem of equality in classical music. Although there are divergences, percussionists perceive that the gender does not influence the professional career, they are optimistic about the existing inequalities and they trust the increase in the female presence in the percussion section. Some of the unexpected contributions of the research are the discrepancies between the data and the perceptions, as well as the debate about the gender influence on the way of playing instruments.
Keywords: Women in percussion; Female instrumentalists; Gender imbalance in orchestras; Female orchestra players; Women in Music